Autoantibodies against complement factor B in rheumatoid arthritis - Matola, Alexandra T.; Fülöp, Angéla; Rojkovich, Bernadette; Nagy, György; Sármay, Gabriella; Józsi, Mihály; Uzonyi, Barbara (Frontiers in Immunology, 2023)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disorder affecting the joints. Many patients carry anti-citrullinated protein autoantibodies (ACPA). Overactivation of the complement system seems to be part of the pathogenesis of RA, and autoantibodies against the pathway initiators C1q and MBL, and the regulator of the complement alternative pathway, factor H, were previously reported. Our aim was to analyze the presence and role of autoantibodies against complement proteins in a Hungarian RA cohort. To this end, serum samples of 97 ACPA-positive RA patients and 117 healthy controls were analyzed for autoantibodies against factor H, factor B (FB), C3b, C3-convertase (C3bBbP), C1q, MBL and factor I. In this cohort, we did not detect any patient with factor H autoantibodies but detected C1q autoantibodies in six patients, MBL autoantibodies in three patients and FB autoantibodies in five patients. Since the latter autoantibodies were previously reported in patients with kidney diseases but not in RA, we set out to further characterize such FB autoantibodies. The isotypes of the analyzed autoantibodies were IgG2, IgG3, IgGκ, IgGλ and their binding site was localized in the Bb part of FB. We detected in vivo formed FB–autoanti-FB complexes by Western blot. The effect of the autoantibodies on the formation, activity and FH-mediated decay of the C3 convertase in solid phase convertase assays was determined. In order to investigate the effect of the autoantibodies on complement functions, hemolysis assays and fluid phase complement activation assays were performed. The autoantibodies partially inhibited the complement-mediated hemolysis of rabbit red blood cells, inhibited the activity of the solid phase C3-convertase and C3 and C5b-9 deposition on complement activating surfaces. In summary, in ACPA-positive RA patients we identified FB autoantibodies. The characterized FB autoantibodies did not enhance complement activation, rather, they had inhibitory effect on complement. These results support the involvement of the complement system in the pathomechanism of RA and raise the possibility that protective autoantibodies may be generated in some patients against the alternative pathway C3 convertase. However, further analyses are needed to assess the exact role of such autoantibodies.